Res Medica, Autumn 1961, Volume 3, Number 1 (Res Medica, 2013)
TABLE OF CONTENTSPERFUSION: Professor W.A. MackeyABDOMINAL CRISES 1: I.S.R. Sinclair, F.R.C.S.FIBRINOLYSIS AND OCCLUSIVE VASCULAR DISEASE: J.D. Cash, B.Sc., M.B., CH.B.RES MEDICATHE UNBORN CHILD: Professor C.S. RussellTHE USE OF CONTROLS IN THE ASSESSMENT OF CLINICAL EVIDENCE: C.V. Ruckley, M.B., CH.B."THE SLIMY MUD OF WORDS":H.C. Drysdale, M.B., CH.B.THE HARVEIAN ORATION, 1961: Dr. J.K. Slater, O.B.E., M.D.MELANCHOLIA: E.B. Ritson, M.B., CH.B.